Contemporary Apocryphal Stories Based on the Life of Prepodobna Stoyna – a Bulgarian Prophetess, Healer, Non-Canonical Saint - Michalska, Aleksandra (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
Prepodobna Stoyna was a Bulgarian prophetess who developed the gifts of preaching and healing after she became blind at the age of 7. At the beginning of the 20th century, Prepodobna Stoyna appeared in the church of Saint George in the village Zlatolist in Southwest Bulgaria, where she subsequently resided for at least twenty years and led the life of a hermit until her death in 1933, at the age of fifty. Stoyna lived in the balcony area inside the church and there, in the room that is preserved and visited until this day, she received pilgrims. According to oral stories and her written vita, she was endowed with the gifts of clairvoyance and healing, as well as levitation, and more. The faithful call her “the sister of St. George” and believe that thanks to her close connection with the saint, she fulfils requests from their prayers even after her death. The Orthodox hurch warns against idolatry and heresy associated with this cult, but, at the same time, this has no effect on the thousands of people visiting this place and treating Prepodobna Stoyna as a saint. In my paper, I point out the cultural mechanisms in the creation of oral stories based on her life, which have similar structural elements to the apocrypha and fulfil similar aims.